2016
DOI: 10.1111/evo.12989
|View full text |Cite
|
Sign up to set email alerts
|

Directional postcopulatory sexual selection is associated with female sperm storage in Trinidadian guppies

Abstract: Female sperm storage (FSS) is taxonomically widespread and often associated with intense sperm competition, yet its consequences on postcopulatory sexual selection (PCSS) are poorly known. Theory predicts that FSS will reduce the strength of PCSS, because sperm characteristics favored before and after FSS may be traded‐off, and opportunities for nondirectional PCSS should increase. We explored these questions in the guppy (Poecilia reticulata), by allowing females to mate multiply and by comparing the paternit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 114 publications
(248 reference statements)
1
25
2
Order By: Relevance
“…We therefore gave priority to maintaining the effective population size in the same range as that used in the previous generations and in other studies (e.g., Ahuja and Singh 2008;Hine et al 2011). We interrupted the experimental evolution experiment after three generations because, due to the variance in the female maturation date (from 70 to 88 days, Reznick and Endler 1982) and the time between mating to first viable parturition (from 21 to 60 days, Devigili et al 2016), it became difficult to distinguish between different generations, which ultimately would have led to generations overlapping within replicates.…”
Section: Experimental Evolution Protocolmentioning
confidence: 99%
“…We therefore gave priority to maintaining the effective population size in the same range as that used in the previous generations and in other studies (e.g., Ahuja and Singh 2008;Hine et al 2011). We interrupted the experimental evolution experiment after three generations because, due to the variance in the female maturation date (from 70 to 88 days, Reznick and Endler 1982) and the time between mating to first viable parturition (from 21 to 60 days, Devigili et al 2016), it became difficult to distinguish between different generations, which ultimately would have led to generations overlapping within replicates.…”
Section: Experimental Evolution Protocolmentioning
confidence: 99%
“…Paternity was assigned using CERVUS v 3.0 (http://www.fieldgenetics.com/pages/home.jsp; Kalinowski, Taper, & Marshall, 2007; Marshall, Slate, Kruuk, & Pemberton, 1998). The data set included 561 offspring (from 36 females, 16 of which produced only the first brood and 20 of which produced two broods) of which 478 (i.e., 85%) were all assigned to one of the two competing FP‐FA males with >95% confidence probability (see Devigili et al., 2016, for more details; Devigili, Evans, Di Nisio, & Pilastro, 2015). The average paternity assignment success for each female was 88%.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite evidence from guppies for inbreeding depression in ejaculate quality (Gasparini et al, 2013;Zajitschek & Brooks, 2010) and competitive fertilization success (Zajitschek et al, 2009), a recent study reported no significant association between heterozygosity and sperm competition success in a laboratory population of guppies (Devigili, Di Nisio, Grapputo, & Pilastro, 2016).…”
Section: Natural Populations Of Trinidadian Guppies (Poecilia Reticulmentioning
confidence: 95%
“…There is also evidence from a recent study of a single Venezuelan population of guppies revealing a highly significant association between microsatellite heterozygosity and orange coloration area (Herdegen, Dudka, & Radwan, ). However, despite evidence from guppies for inbreeding depression in ejaculate quality (Gasparini et al., ; Zajitschek & Brooks, ) and competitive fertilization success (Zajitschek et al., ), a recent study reported no significant association between heterozygosity and sperm competition success in a laboratory population of guppies (Devigili, Di Nisio, Grapputo, & Pilastro, ).…”
Section: Introductionmentioning
confidence: 97%